PENGARUH KAPUR TOHOR TERHADAP PENURUNAN KADAR ZAT BESI (FE) PADA AIR TANAH DALAM (SUMUR BOR) DI KABUPATEN CIREBON - Loura Weryco Latupeirissa (LPPM ITEKES Mahardika, 2018)
Background: Groundwater often contains large amounts of iron (Fe) which can cause health problems such as nausea, high doses can damage the intestinal wall, and lead to death. The threshold value of drinking water containing iron (Fe) is 0.3 mg / l and clean water is 1 mg / l. The use of addition of quicklime according to theory can only reduce stabilize pH, reduce turbidity, and reduce organic matter. In this study the researchers wanted to try adding quicklime to reduce levels of iron (Fe) in deep groundwater. Purpose. This research aims to determinethe effect of Quicklime to Decrease Iron (Fe) Levels On Well Drilling In The Cirebon District Method: This type of research is an experimental design with pre-experimental design, with the design of one group pretest-posttest design. The sample in this study were 5 samples. Data analysis used is bevariat and univariate analysis with Wilcoxon signed rank test. Result: The results showed that the average iron content before treatment was 0.126 and after treatment was 0.02. The results of the Wilcoxon signed rank test were obtained p value = 0.042 (p <0.05). This means that there is a significant effect of lime on reducing iron content .